Strategi Peningkatan Pajak Restoran pada Masa Pandemi Covid-19 di Kota Bogor - Nia Daliati Ahjat; A Faroby Falatehan; Dedi Budiman Hakim (Institut Pertanian Bogor, 2022)
The purpose of this study was to analyze the impact of covid 19 on restaurants, calculate potential income of restaurants and formulate a strategy for increasing restaurant taxes during the Covid-19 pandemic in Bogor City. The research population was 633 restaurants. Samples were taken based on the Slovin formula as many as 87 restaurants. The analytical methods used are descriptive statistics, multiple linear regression analysis (cross section data), IFAS-EFAS Matrix, SWOT, and QSPM. The results showed that Covid-19 had an impact on a decreasing income, a decrease in the number of customer visits, and a decrease in the number of workers at restaurants in Bogor City. The potential for restaurant taxes during the Covid-19 pandemic in Bogor City based on survey results were 111.3 billion rupiah. Factors affecting restaurant income in Bogor City during the Covid-19 pandemic were the number of customer visits, the number of workers, and promotional activities. The main strategy for increasing restaurant taxes during the Covid-19 pandemic in Bogor City is updating restaurant data regularly. Keywords: Bogor city, covid-19, restaurant tax